Flyping conjectur - Azram, Mohammad (Publications International, 2013)
In this paper we will establish the Tait’s flyping conjecture “two reduced alternating knots are equivalent iff they can be converted into one another by flypes” by generalizing Reidemeister moves especially Reidemeister move of type II and therein its consequent applications.